Efektivitas Pelaksanaan Festival Jelajah Maumere (FJM) Sebagai Media Promosi Wini Ronan (G) (Lumbung Benih) oleh Dinas Pariwisata Kabupaten Sikka - Niron, Samuel Klaudius Sabon; Carcia, Maria Silvana M.; Margaretha Yulianti (Jurnal Projemen UNIPA, 2026)
This study aims to determine the effectiveness of the Festival Jelajah Maumere as a medium for promoting Wini Ronan (G) by the Sikka Regency Tourism Office. The method used in this study is qualitative descriptive research. The subject of this study is the implementation of the Maumere Exploration Festival as a means of promoting tourism in the region. The research informants were selected purposively based on their involvement and knowledge of the festival activities, including officials or staff from the Sikka Regency Tourism Office, tourists, and community leaders. Data collection was conducted using several techniques, including interviews, observation, and documentation. The data were analyzed qualitatively through the following stages: data reduction, data presentation, and conclusion drawing. The results of the study demonstrate that the Festifal Jelajah Maumere has been effective in increasing tourist visits, generating interest in repeat visits, and having a positive impact on MSMEs, as evidenced by increased income and sales during the festival.